ANALISIS HARMONISASI AKUNTANSI DI INDONESIA - Wirawan Endro Dwi Radianto (Jurnal Riset Akuntansi dan Keuangan, 2006)
Recently, accormting harmonizatiot become big issue and has continued to spread oomd the world. Tlrc objective of this study is to investigote the degree of national rccourting hirmonization in Indonesia.Empirical study is conducted by using several accounting valuation such as cashflow vahdion of inventory, deprcciation, and segment rcpnrting. Basic in&tstry otd chemical, various in&utry, and consumer gool ittdustry oe used re smryel. It is found tlut in many respects most comlreties use Mbwt ,rwtWs except cash flow rcporting.It is too eorly to corrclude that ffiional hmmonization l:us takenplrce in btdonesia Bur tlu progrrrs of ,tdiorrol humonizotiott is stitl in process.Keywords: accowtting humoniz.Aion, national harmonization,H-Indeks